The Legal Protection for Folk Songs from Unknown Origin: Orientation and Formulation in the Perspective of Legal Cybernetics - Indrawan, I Komang Gede; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The existence of the phenomenon of regional songs whose regional origins are unknown has led to legal problems in the form of a legal vacuum regarding legal protection. Existing laws and regulations are still missing in providing arrangements regarding regional songs whose regional origin is unknown.Purposes of the Research: This study aims to analyze and at the same time seek legal protection through special arrangements regarding regional songs whose regional origins are unclear.Methods of the Research: Normative legal research with a conceptual and statutory approach.Results of the Research: The orientation to provide legal protection for folk songs of unknown origin can actually be carried out by issuing specific implementing regulations that regulate and facilitate folk songs of unknown origin to obtain legal protection. Legal protection for folk songs of unknown origin in the perspective of legal cybernetics can be carried out by establishing special regulations, research and studies, as well as cultural titles and festivals for folk songs of unknown origin. This is because legal protection for folk songs of unknown origin based on a legal cybernetics perspective needs to be carried out, especially by involving the political will of the local government and local cultural figures.